Corporate Governance research in Ghana through bibliometric method: review of existing literature - Isaac Francis Antwi; Carla Carvalho; Cecília Carmo (Cogent Business & Management, 2022)
There has been a growing concern about corporate governance (CG) studies in Ghana amongst various scholars, but the same cannot be said of a specific discipline area. Therefore, this paper presents a review of research through the Scopus database. The objective is to use bibliometric analysis and VOSviewer network visualisation to explore multiple subject areas and provide the current state of CG research to understand the evolving trend of the research field through existing literature. In addition, it aims to use the scientific method to identify hotspot keywords direction, impactful corporate governance studies direction and provide some additional insight into the summary findings for future research. The study contributes to the extant literature by focusing on annual production, author's network collaboration, journals, keywords co-occurrence, and impactful CG articles in Ghana. We found bibliometric analysis and network collaboration have uncovered the critical research domain and given more meaningful results. Moreover, research interest in corporate governance studies in Ghana has grown by yearly production, authors production, and citations. In addition, summary results find hotspot keywords are corporate social responsibility, corporate ownership, and firm performance. Furthermore, 40 papers resulted as most impactful and provided board structure and firm performance are the trending topics mostly studiedOn the other hand, a few keywords search areas are compliance, political connection, mandatory and voluntary disclosures, dividends, audit committee, and gender diversity.
Keywords: 650; VOSviewer; bibliometric analysis; Corporate Governance; Keywords Ghana